Improvement QCM Quality By Polystyrene Coating and Bovine Serum Albumin as Immobilization Agent - Didik, Lalu A.; Yahdi, Yahdi; Masruroh, Masruroh (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
Polystyrene (PS) thin film with various concentration of mass (1%, 3%, and 5%) has been deposited onto Quartz Crystal Microbalance (QCM) surface by a spin coating method. The purpose of this research is the improvement of Bovine Serum Albumin (BSA) immobilization into the QCM surface. The QCM resonance frequency has been investigated by means of Impedance Analyzer. The film thickness was calculated by the Sauerbrey equation. The surface roughness of the PS layer was observed by noncontact Topography Measuring System (TMS-1200). Calculation result using a Sauerbrey equation shows the thickness of the PS layer increases with the increasing PS concentration. The QCM/PS with 1% and 5% concentration of mass has rougher morphology and more frequency shifts caused by BSA injection compared to 3% concentration of PS.